Association between smoking and body mass index among males aged 20 years and above: A study in rural Tamil Nadu, South India (South East Asia Journal of Public Health, 2015)
A large number of epidemiological studies reported an increase in mortality due to cancer and other diseases among lean individuals. In this paper we aimed to investigate the relationship between smoking status and Body Mass Index (BMI) in men aged 20 years and above. A cross sectional study was conducted in the rural field practice area of the Department of Community Medicine, PSG Institute of Medical Science and Research, Coimbatore during June and July 2010. A total of 459 men aged 20 years and above were included in the study. Statistical analyses were done using the General Linear Model procedure of SPSS. We observed that cigarette smokers weighed (Kg) less, p